BS EN 61753-053-02. Fibre optic interconnecting devices and passive components. Performance standard. Part 053-02. Non-connectorized single-mode fibre, electrically controlled, variable optical attenuator for category C. Controlled environments (28th May 2021) - British Standards Institution,
No abstract available